Inwestycje infrastrukturalne w rozwoju lokalnym - Witkowski, Krzysztof (Infrastructure Investments In Local Development, 2008)
The influence of infrastructure on local and regional development is plain. Similarly, the local development determines the development of infrastructure. In the paper there is presented the influence of infrastructure on local development, particularly there is showed the meaning of infrastructure in the commune development and as well the activities of local authority in the development of infrastructure. Infrastructure is the most important instrument of influence of local policy on economic processes, because it is adapted to the needs of the user of commune. It also creates the chances for its dynamics and development. The size and speed of local development depend on the skills of local (commune) management and the skills of gaining founds for the infrastructure.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 338-345